2022
DOI: 10.1155/2022/7636458
|View full text |Cite|
|
Sign up to set email alerts
|

Piano Intelligent Teaching Evaluation with IoT and Multimedia Technology

Abstract: With deepening of the economic development process, the overall spiritual and cultural needs of the people have increased, and quality education has received more and more attention. Piano education is an important part of quality education. Nowadays, piano education has also been able to move forward continuously. As the king of musical instruments, the piano is widely used in music learning. Learning the piano can exercise willpower, develop intelligence, and cultivate sentiment. With development of computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The Back Propagation Algorithm network uses the improved Artificial Fish Swarm Algorithm (IAFS) to address the drawbacks of the BP network. The Study has conducted a thorough and systematic investigation to confirm the usefulness and viability of IAFS-BP applied to quality evaluation of intelligent piano instruction in the environment of the IoT and multimedia [24]. The case study showed statistically significant improvement in Blended Piano Teaching Model.…”
Section: Figure 1: Structure Of Piano Education Platformmentioning
confidence: 96%
“…The Back Propagation Algorithm network uses the improved Artificial Fish Swarm Algorithm (IAFS) to address the drawbacks of the BP network. The Study has conducted a thorough and systematic investigation to confirm the usefulness and viability of IAFS-BP applied to quality evaluation of intelligent piano instruction in the environment of the IoT and multimedia [24]. The case study showed statistically significant improvement in Blended Piano Teaching Model.…”
Section: Figure 1: Structure Of Piano Education Platformmentioning
confidence: 96%
“…Thirdly, learning the Piano helps in the development of a healthy lifestyle and spirituality. Fourth, learning the Piano can help with self-control and psychological awareness [3]. Figure 1 depicts the multimedia music recognition module for the Piano.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the classroom, AI technology offers opportunities for language immersion through virtual reality (VR) experiences and language exchange platforms, enabling students to practice English in authentic contexts and interact with speakers from around the world [18]. The integration of AI in English language teaching empowers both educators and learners, fostering more efficient, personalized, and immersive learning experiences that ultimately lead to greater language proficiency and fluency [19]. Integrating artificial intelligence (AI) technology into the construction of a university music education teaching system holds immense potential to transform the way music is taught and learned [20].…”
Section: Introductionmentioning
confidence: 99%